Population dynamics and adaptive strategies of Martiodrilus carimaguensis (oligochaeta, glossoscolecidae), a native species from the well-drained savannas of Colombia - Jiménez Jaén, J.J.; Moreno, Alonso; Lavelle, Patrick M.; Decaëns, Thibaud (International Center for Tropical Agriculture, 2001)
Martiodrilus carimaguensis (Oligochaeta, Glossoscolecidae) is a large, anecic native earthworm species which was found in natural and disturbed savannas in the Oxisols of the Colombian Llanos. The population dynamics of this species were studied in a native savanna, and in a 17-year-old grazed grass-legume-pasture where density and biomass were higher. Monthly cast deposition on the soil surface in the improved pasture was 38.4x10 3 fresh casts/ha, 11 times greater than in the native savanna. A strong relationship was found between numbers of M. carimaguensis and numbers of fresh surface casts. Different patterns of adaptation to the dry season were observed for adults and juveniles. Adults are active for 8 months whereas juveniles enter diapause 3-4 months earlier. The vertical distribution pattern of the earthworm population also shows marked seasonal changes.